ANALISIS LINGUISTIK KLINIS: GANGGUAN BERBAHASA PADA PENYANDANG SUMBING DI MEDIA SOSIAL TIKTOK @ORANGKAMPUNGATM2 PERSPEKTIF BAHASA SUNDA - Alhafidz, Zidan Rizka (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
This study analyzes language disorders in individuals with cleft lip and palate from a phonological perspective, using a case study of the TikTok account @orangkampungatm2 in the context of the Sundanese language. A qualitative narrative approach was used as the methodological framework, with data collection through observation and note-taking of videos uploaded by the subject of the study. The analysis results show that the cleft condition affects the individual's phonetic abilities, particularly in the articulation of bilabial, nasal, and fricative sounds in Sundanese. These sound distortions are caused by the subject's inability to fully close their lips due to the cleft in the lip area. Furthermore, cleft lip and palate also impact suprasegmental aspects such as intonation and prosody (stress). These findings highlight the linguistic challenges faced by individuals with cleft lip and palate and the role of social media in raising public awareness of linguistic diversity. This research provides a detailed overview of the phonetic characteristics of speech in individuals with cleft palate in the Sundanese language, while also demonstrating how social media can serve as a valuable data source for clinical linguistic studies